HISTORICAL DEVELOPMENT OF DIGITAL PHOTOGRAMMETRIC AERIAL SENSOR CALIBRATION - Kayi, Abdullah; Bayram, Bulent; Seker, Dursun Zafer (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2021)
The description of the system calibration in the academic community was provided in 1963. This definition has been used in many scientific fields where the measurement or surveying was made. From this point of view, there arc lots of scientific studies that were published about calibration, especially aerial sensor calibration in photogrammetry field. With the contributions to these studies, many unknown topics were solved and shared, and so relevant views were presented. Most of the articles were published between the years of 2001-2004 when GNSS/IMU integated system was begun to be used in aerial photogrammetry. This particular study. covered 38 of the 76 articles published in that time period. In this paper, the photogrammetric aerial sensor calibration studies are examined beginning from 1963 to 2019. most of the records in the literature are searched and indexed according to their topics. The issues reached on the consensus or dissensus are listed and the open-ended questions are discovered.
Keywords: Boresight Calibration; Stability; System Calibration; GNSS Drift; Lever-Arm; CAMERA CALIBRATION; Environmental Sciences & Ecology